Scaffolding to Help Numeracy Literacy Mild Mental Retardation Children on The Introduction of The Value of Money - Amazia Ananta Prabaswara; Fika Widya Pratama (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
The existence of ABK (Children with Special Needs) in inclusive schools still requires assistance from accompanying teachers. However, the limited number of accompanying teachers causes the learning process of ABK to be not optimal, including in improving numeracy literacy skills regarding the introduction of the value of money. Therefore, this study aims to assist in the form of scaffolding for mild mental retardation who attend inclusive schools at SMP N 1 Salatiga in the 2022-2023 academic year. Research begins with identifying initial capabilities, types, and causes of errors followed by implementation scaffolding right. This qualitative research data collection technique includes test methods, interviews, and documentation with a method and time triangulation process. The results showed that the subject experienced misunderstanding, transformation, and process skills. The same type of error, with different causes, can result in different scaffolding given. Scaffolding that succeeds in helping Mild Mental retardation in recognizing the value of money is level 1 (Environmental Provisions), level 2 by type Explaining and Restructuring as well as Scaffolding level 3 (Developing Conceptual Thinking).Keberadaan ABK di sekolah inklusi, tetap memerlukan pendampingan dari guru pendamping. Akan tetapi, terbatasnya jumlah guru pendamping menyebabkan tidak optimalnya proses belajar ABK termasuk dalam meningkatkan kemampuan literasi numerasi akan pengenalan nilai uang. Oleh karena itu, penelitian ini bertujuan untuk memberikan bantuan berupa scaffolding terhadap Tunagrahita Ringan yang bersekolah di sekolah inklusi SMP N 1 Salatiga pada TA 2022-2023. Penelitian dimulai dari pengidentifikasian kemampuan awal, jenis dan penyebab kesalahan yang dilanjutkan dengan pengimplementasian scaffolding yang tepat. Teknik pengumpulan data penelitian kualitatif ini mencakup metode tes, wawancara dan dokumentasi dengan proses triangulasi metode dan waktu. Hasil penelitian menunjukkan bahwa subjek mengalami kesalahan pemahaman, transformasi dan keterampilan proses. Jenis kesalahan yang sama, dengan penyebab yang berbeda, dapat mengakibatkan perbedaan scaffolding yang diberikan. Scaffolding yang berhasil membantu Tunagrahita Ringan dalam mengenal nilai uang adalah level 1 (Environmental Provisions), level 2 dengan jenis Explaining dan Restructuring serta Scaffolding level 3 (Developing Conceptual Thinking).